OMIP‐061: 20‐Color Flow Cytometry Panel for High‐Dimensional Characterization of Murine Antigen‐Presenting Cells. Issue 12 (19th August 2019) - DiPiazza, Anthony T.; Hill, Juliane P.; Graham, Barney S.; Ruckwardt, Tracy J.
Abstract: This 20‐color flow cytometry panel was designed to resolve the cellular heterogeneity of antigen‐presenting cells and was optimized for lymph node tissue. Reagents were carefully selected and optimized for identification of B cells (B220), neutrophils (Ly6G), monocytes and macrophages (Ly6C, CD169, F4/80), and dendritic cells (XCR1, CD172a, CD11c, I‐A/I‐E, CD24, CD64, pDCA‐1, CD103, CD11b). Inclusion of additional functional markers involved in cell migration (CCR7), co‐stimulation (CD80), and adhesion (ICAM‐1) enabled further phenotypic characterization. Finally, this panel has been tested and is compatible with fluorescently labeled antigens such as Alexa Fluor 488 (Ax488) for the study of antigen‐bearing cells in vivo. Published 2019. This article is a U.S. Government work and is in the public domain in the USA. Abstract :